Factors Regulating Year‐Class Strength of Silver Carp Throughout the Mississippi River Basin. Issue 3 (May 2018) - Sullivan, Christopher J.; Weber, Michael J.; Pierce, Clay L.; Wahl, David H.; Phelps, Quinton E.; Camacho, Carlos A.; Colombo, Robert E.
Abstract: Recruitment of many fish populations is inherently highly variable interannually. However, this variability can be synchronous at broad geographic scales due to fish dispersal and climatic conditions. Herein, we investigated recruitment synchrony of Silver Carp Hypophthalmichthys molitrix across the Mississippi River basin. Year‐class strength (YCS) and synchrony of nine populations (maximum linear distance = 806.4 km) were indexed using catch‐curve residuals correlated between sites and related to local and regional climatic conditions. Overall, Silver Carp YCS was not synchronous among populations, suggesting that local environmental factors are more important determinants of YCS than large‐scale environmental factors. Variation in Silver Carp YCS was influenced by river base flow and discharge variability at each site, indicating that extended periods of static local discharge benefit YCS. Furthermore, river discharge and air temperature were correlated and synchronized among sites, but only similarities in river discharge were correlated with Silver Carp population synchrony, indicating that similarities in discharge (i.e., major flood) among sites can positively synchronize Silver Carp YCS. The positive correlation between Silver Carp YCS and river discharge synchrony suggests that regional flood regimes are an important force determining the degree of population synchrony among Mississippi River Silver Carp populations.